Effect of inner liner material on penetration behavior of reactive material double-layered liner shaped charge. (March 2020) - Guo, H G; He, S; Ma, H B; Sun, T; Zheng, Y F
Abstract: To improve the insufficient penetration depth of the traditional single reactive liner shaped charge, the penetration enhancement behaviors of a reactive material double-layered liner (RM-DLL) shaped charge are investigated. This RM-DLL consists of an inner liner with metal materials and an outer liner with (polytetrafluoroethylene) PTFE/Al reactive materials. Based on the platform of AUTODYN-2D code, the influence of inner liner material on the jet formation of RM-DLL shaped charge and its penetration performance of multi-layered space plates were conducted. The numerical results indicated that, during the jet formation stage, the inner metal liner mainly formed a high-velocity precursor jet and the outer reactive liner became a major part of the slug. With increasing the material density of inner liner, the jet tip velocity and tip diamater decreased, and the effective mass of precursor jet also dropped off. For a given penetration time, with the increase in the material density of inner liner, the penetration capability of the RM-DLL shaped charge increased, whereas the mass of reactive materials entering the penetrated steel target decreased significantly. This RM-DLL shaped charge, incorporating the penetration capability of a precursor metal jet and the deflagration effects of the follow-thru reactive materials, will produce extremely damage to the desired target, typically such as the armored fighting vehicles.